Is cognitive decline in the elderly associated with contextual income? Results of a population-based study in southern Brazil - Ana Lúcia Danielewicz; Katia Jakovljevic Pudla Wagner; Eleonora d'Orsi; Antonio Fernando Boing (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2016)
Abstract: The aim of this study was to estimate the association between contextual income and cognitive decline in the elderly in Florianópolis, a medium-sized city in southern Brazil. A nested cross-sectional study was performed in a cohort of elderly ≥ 60 years (n = 1,197), interviewed in the second wave (2013/2014) of the EpiFloripa cohort. Cognitive decline was assessed with the Mini Mental State Examination (MMSE) and contextual income was measured as the mean monthly income of the heads of households. Individual adjustment variables were sex, age, skin color, per capita household income, years of schooling, and time living in the neighborhood. The data were analyzed using multilevel logistic regression. The odds of cognitive decline were twice as high (OR = 1.99; 95%CI: 1.03; 3.87) in elderly living in census tracts with the lowest income quintile compared to those in the highest quintile, independently of individual characteristics. In conclusion, the socioeconomic environment is related to cognitive decline and should be considered in public policies with a focus on health of the elderly.